PWE-129 Treatment of achalasia in patients with oesophageal varices: an international case series. (17th June 2017) - Magee, C; Holloway, R; Gyawali, P; Roman, S; Pioche, M; Savarino, E; Quader, F; Bredenoord, A; Sweis, R
Abstract : Introduction: Achalasia is a chronic condition presenting with dysphagia, regurgitation, chest pain and/or weight loss. Management options include Heller's myotomy, Botox, pneumatic dilatation and Per-Oral Endoscopic Myotomy (POEM). Treatments carry risks of bleeding and perforation. Concomitant portal hypertension with varices is very rare and achalasia treatment in this context has only been described in single case reports. Method: Experience from physicians/surgeons treating these disorders was sought through the International Manometry Working Group. Results: 13 patients with portal hypertension from 6 international centres have been collected; mean age 61±9 years. The median pre-therapy Eckardt score was 7 (IQR 6–9). 9/13 (69%) patients had a barium swallow and 12/13 (92%) had oesophageal physiology studies performed. There were 3 Type I, 6 Type II, 2 Type III achalasia and 2 with oesophago-gastric outflow obstruction. Varices were identified endoscopically in 7 patients, radiologically in 5 and in 1 patient varices were first noted during surgical myotomy. 2 patients had grade 3 varices, 3 had grade 2 and 3 had grade 1 varices (grading not provided for the rest). Cirrhosis was due to alcohol in 7 patients, non-alcoholic steatohepatitis in 3, cryptogenic in 2 and 1 had hepatitis C cirrhosis. 75% were Child-Pugh A and 25% were Child-Pugh B. Patients had diverse treatments for achalasia. 4 were treated with Botox injections (1 with EUS), 4 had dilation alone, 3 received a POEM, another had POEM then dilation and 1 patient had Botox followed by Heller's myotomy. 3 patients underwent variceal eradication in advance; all had banding first but in 2 patients superficial eradication was followed by a transjugular intrahepatic portosystemic shunt (TIPSS) before endoscopic dilation. All patients had symptomatic improvement with median Eckardt score post intervention=1 (IQR 0–2) p<0.0001 compared to baseline. A matched group of 20 patients who underwent treatment for achalasia (all subtypes) but without varices had similar outcomes (p=NS). No patients had recorded complications of bleeding or perforation; however both patients who had TIPSS had temporary hepatic decompensation. Conclusion: This reports 13 patients from international centres who have had interventions for achalasia on the background of oesophageal varices. None had bleeding complications despite only 3 having variceal eradication. Symptom response mirrored those who undergo standard achalasia therapy, regardless of the severity of varices, treatment modality provided or achalasia subtype. Disclosure of Interest: None Declared